The Problem of Neutrality of the State Civil Apparatus (ASN) in the 2020 Regional Head Election - Muhammad Eko Atmojo; Tunjung Sulaksono; Nita Ariba Hanif; Helen Dian Fridayani (Universitas Muhammadiyah Ponorogo, 2023)
This article will discuss the neutrality of bureaucracy in Indonesia with the perspective of data collection from online media. Where the purpose of this paper is to find out the involvement of ASN in the power struggle in the implementation of regional head elections. If we look at the many cases of neutrality violations that occurred in the 2020 regional head elections, this is also justified by the State Civil Affairs Commission which records cases of violations of bureaucratic neutrality. The implementation of regional head elections conducted in 2020 is indeed full of pros and cons, besides that almost every regional head election always arises the issue of bureaucratic neutrality. In 2020, there were 694 ASNs who committed violations and have been reported to the State Civil Apparatus Commission. This shows that the implementation of regional head elections is one of the momentums for candidates for regional heads and ASNs to conduct patron-client practices. In addition, the implementation of regional head elections is also carried out during the covid-19 pandemic so that it is possible to have ASN involvement in the implementation of campaigns and so on. Because in 2020 there is a lot of involvement of civil apparatus that shows open support to one of the candidates.